PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA PADA PT. BNI KCU USU TBK - Muadz Qemal Siddiq; Bintang Trinitati; Devi Yusvita Br. Tambunan; Maria Elisabeth Napitupulu; Wilson Alfredo; Yovie Ernanda (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2020)
Research, to study leadership style, organizational culture, and job satisfaction on employee performance at PT BNI KCU simultaneously or partially. The research method uses quantitative descriptive analysis. The population in this study were all companies that gathered 80 people. The technique of determining samples uses the saturation sampling technique. Data analysis techniques using the F Test, T Test, and Multiple Linear Regression. Based on the results of data analysis in the study shows the partial leadership style (X1) has a tcount of 0.275 and a ttable value of 1.664 then the tcount> ttable (0.275> 1.664) with sig.0.784 <0.05. This states the rejected hypothesis, namely: the partially and significantly agreed leadership style of employee performance at PT BNI KCU. Organizational culture (X2) has a tcount of 2.715 and a ttable value of 1.664, then a tcount> ttable (2.715> 1.664) and sig. 0.08 <0.05. This states the accepted hypothesis, namely: A positive and significant organizational culture for employees at PT BNI KCU. And job satisfaction (X3) has a t-test of 0.096 and a t-table value of 1.664, then a t-value> t table (0.096> 1.664) and sig. 0.924 <0.05. This states the rejected hypothesis, namely: Job satisfaction that is not positive and significant for employee performance at PT BNI KCU.